Anodic molecular hydrogen formation on Ru and Cu electrodes. Issue 20 (10th September 2020) - Scott, Soren B.; Engstfeld, Albert K.; Jusys, Zenonas; Hochfilzer, Degenhart; Knøsgaard, Nikolaj; Trimarco, Daniel B.; Vesborg, Peter C. K.; Behm, R. Jürgen; Chorkendorff, Ib
Abstract : On important electrocatalysts including ruthenium and copper, increasing the potential pushes adsorbed hydrogen off as H2, an unexpected uphill desorption. Abstract : Electrochemical hydrogen adsorption and desorption, and the state of adsorbed hydrogen (*H) on metal surfaces are of fundamental interest as well as practical importance for the hydrogen evolution reaction (HER) and electrochemical hydrogenation reactions including CO2 and CO electroreduction. Here, we report a previously undiscovered phenomenon whereby *H desorbs as H2 during an anodic potential sweep at potentials anodic of (more positive than) the equilibrium potential of U 0 (H2 /H + ), hence at potentials where hydrogen desorption would be expected as H + . Using electrochemistry – online mass spectrometry, we observe, quantify, and characterize the phenomenon on two different materials in two different environments – Ru(0001) in acid and polycrystalline Cu in alkaline. For both Ru and Cu, the anodic H2 formation seems to coincide with *OH adsorption, which would be consistent with a displacement mechanism. We propose that a high barrier for the Volmer step causes some of the displaced *H to desorb as H2 (Tafel step) rather than the thermodynamically more favorable desorption as H + (Volmer step).